Properties of Zinc alloy cast product with different composition of Silica Sand and Bentonite in Green Sand Mould - Zatil Alyani, Mohd Amin; Faizul, Che Pa; Mohd Ichwan, Nasution, P.M Ir. (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.